La messa in valore del patrimonio storico nel Piano paesaggistico della Regione Toscana - Gisotti, Maria Rita (Scienze del Territorio, 2017)
The Tuscan Landscape plan reads the dimension of history in a coevolutionary way between the man and the environment. To illustrate the consistency of these processes and their outcomes, the Plan has prepared a number of products, from the landscape heritage maps to the studies included in the “Interpretive description” concerning the great phases of geological structuring, those of territorialisation and the ‘artialisation’ processes - as the French would call it. Moreover, the Plan has devoted a dedicated study to the historical landscapes, tracing the founding matrices of the  current configurations. The historical landscape structures identified and described in these products have a testimonial, cultural and aesthetic-perceptual value which is at once a functional and economic one. They contain principles of sustainable use of territories concerning hydro-geomorphologic balance, settlement stability and quality, preservation of biodiversity and ecological connectivity, the agricultural productivity functions and so on. Principles that the Plan aimed at re-actualizing as rules ordinarily orientating territorial transformation. In this view, the Plan suggests an interpretation of landscape heritage as a carpentry of innovation, as a framework on which we can build the future territorial and landscape project.